Literature Study of Formulating and Testing Physical Properties of Hand Sanitizer Preparations of Various Plant Extracts - Susi Yanti; Cory Linda Futri (Journal of Public Health and Pharmacy, 2022)
Hand sanitizers are widely used for practical reasons when there is no water. Hand sanitizer is easy to carry and can be used quickly without the use of water. According to the US FDA (Food and Drug Administration) the advantages of hand sanitizers are that they are able to kill germs in a relatively fast time. The use of antiseptic gels that contain alcohol can cause irritation so it is not safe to be used again, it is necessary to use antiseptics made from nature or containing natural ingredients that are safe when applied to the surface of the hands repeatedly. The purpose of this literature study is to determine the formulation of hand sanitizer gel and test the physical properties of various plant extracts based on a literature study. The method used in this research is a study of literature from 6 journals, both national journals indexed by sinta 1-4 and international journals indexed by Scopus related to the title of the proposed research, namely the study of the formulation literature and testing the physical properties of hand sanitizer gel preparations from oil Nutmeg Essentials, Noni leaf extract, Trembesi leaf extract, Bay leaf extract, Cucumber extract, Papaya leaf extract. In the study of making hand sanitizers from various extracts, it can be concluded that the hand sanitizer gel that was formulated met all the requirements for evaluating the physical properties of the gel which included organoleptic, homogeneity, and pH tests, while for dispersion and adhesion there were those that did not meet the standards.